Contrasting drivers of diversification rates on islands and continents across three passerine families - Conway, Meaghan (Proc Biol Sci, 2019)
Diversification rates vary greatly among taxa. Understanding how species-specific traits influence speciation rates will help elucidate mechanisms driving biodiversity over broad spatio-temporal scales. Ecological specialization and range size are two hypothesized drivers of speciation rates, yet each mechanism predicts both increases and decreases in speciation. We constructed a continuous index of specialization using avian bill morphology to determine the relative effect of specialization and range size and shape on speciation rates across 559 species within the Emberizoidea superfamily, a morphologically diverse New World clade. We found a significant positive correlation between specialization and speciation rate and a negative correlation with range size. Only the effect of specialization persisted after removing island endemics, however, suggesting that ecological specialization is an important driver of diversity across large macroevolutionary scales, and the relative importance of specific drivers may differ between islands and continents.